The State of Financial Reporting of Philippine Listed and Government Banks - Cayanan, Arthur (Philippine Management Review; Vol 19 (2012))
This study compares the financial reporting practices of Philippine listed and government banks with respect to their compliance with the generally accepted accounting principles.  The state of external audit for both categories of banks is also discussed in this paper.  The findings show that the financial reporting practices of listed banks are not better than those of government banks.  The implementation of the international accounting standards in 2005 resulted in the improvement of disclosures related to financial assets and liabilities, especially loans receivable.  In spite of this improvement, cases of non-compliance are still observed, some of which can overstate assets and net income.
Keywords: financial reporting disclosures, loans receivable, provision for bad debts, impairment losses, audit opinion